Scanning Electron Microscopy Techniques in the Analysis of Gunshot Residues: A Literature Review - Matteo Antonio Sacco; Saverio Gualtieri; Agostinho Santos; Bárbara Mendes; Roberto Raffaele; Alessandro Pasquale Tarallo; Maria Cristina Verrina; Francesco Ranno; Maria Daniela Monterossi; Pietrantonio Ricci; Isabella Aquila (Applied Sciences)
The analysis of gunshot residues (GSRs) is a critical component of criminal investigations, linking suspects to firearms or shooting incidents. Among the various analytical techniques employed, scanning electron microscopy (SEM) has emerged as a valuable tool due to its ability to provide high-resolution imaging and detailed elemental composition analysis of GSR particles. Recent technological advancements have significantly enhanced the effectiveness of SEM in GSR analysis, incorporating improved detectors and software that facilitate the more accurate detection and characterization of GSR particles. To ensure the reliability of SEM-based GSR analysis, it is essential to adhere to established methodologies for sample collection and preparation, as well as to implement best practices in data interpretation within the forensic context. Through a narrative review, this paper aims to explore the application of SEM techniques for GSR analysis, elucidate the methodological approaches that underpin effective forensic investigations, and highlight the advantages and limitations of SEM, thereby addressing the ongoing challenges and opportunities in the field.